TENGGELAMNYA JAKARTA DALAM HUBUNGANNYA DENGAN KONSTRUKSI BANGUNAN BEBAN MEGACITY - Manik, Jack M; Marasabessy, M Djen (UI Scholars Hub, 2010)
Sinking of Jakarta in Relation with Building Construction Namely Megacity Load. The Jakarta city which lies on low coastal plain is home of over ten millions mof people. The number of population has been growing together with the constructions of high rise buildings. The buildings with all of the materials and people who live and use them together with continuous ground water extraction have resulted in undergone dramatic subsidence and other following negative impacts such as permanent flooding. This paper explicitly propose a hypothesis that the total weight of the megacity and the population tends to cause subsidence in coastal area and the charge in the earth isostasi, as well as in earth rotation.